A TRANSLATION ANALYSIS ON IDIOMATIC IN BOAT SONG BY ED SHEERAN BASED ON LARSON’S THEORY - I Kadek Yuda Darmadi Putra (LPPM Universitas Dhyana Pura, 2023)
This study aims to find idiomatic and determine the idiomatic translation used in the lyricsof boat song by Ed Sheeran based on Larson's theory. A qualitative descriptive method wasused in this study to collect and analyze data from song lyrics. The data source is the song ofboat song by Ed Sheeran which released in 2023. Larson's (1984) theory of idiomatictranslation and fairness in translation is used to analyze the data. From the analysis, it wasfound that idiomatic expressions were found and each has a different level of naturalness,based on Larson's theory. There are very natural levels, natural levels, and less natural levelsfound from data. In this research, the data that has been found and collected is five verses ofthe lyrics of the song Boat by Ed Sheeran. From the five stanzas, five idiomatic translationwere found and each has a different level of naturalness, based on Larson's theory. There arevery natural levels, natural levels, and less natural levels that are found from the data. Twoidioms which are classified as very natural, namely the verses